HUBUNGAN NEGARA DAN AGAMA (STUDI PADA IMPLEMENTASI PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 2 TAHUN 2013 TENTANG KEBIJAKAN GERAKAN MASYARAKAT MAGRIB MENGAJI DI KECAMATAN BANGKINANG TAHUN 2014-2015) - Muhammad Damsir Saputra; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation Kampar District Regulation No. 2 of 2013 About Policy Society Movement seeks to boost Maghreb recite the Qur'an reading culture through Maghrib Society Movement Program assesses, is expected to help improve the public's penchant recite back after sunset. This research was conducted in the District Bangkinang Kampar regency. The data used in this study is Primary data and secondary data. Data collection through in-depth interviews and documentation. Descriptive Qualitative methods in use due to the retrieval of data from informants depth interviews of informants related. So that the problem in this case is Does the Government understand Kampar District Regulation No. 2 of 2013 About Policy Society Movement Maghrib Koran in District Bangkinang years 2014-2015 and Is Social Environment, Politics and Culture supports Kampar District Regulation No. 2 of 2013 About Policy Peoples movement Maghrib Recite in District Bangkinang years 2014-2015.Identify the problem in the achievement of them: Low intensive monitoring of the relevant parties both from the local government, civil servants, non-civil servants Nor Village Government As well as the extension of Religion in the implementation of District Regulation Kampar No. 2 in 2013 About Policy Society Movement Maghrib Recite in District Bangkinang the number of people who do not obey the Regional Regulation and prefer to perform other activities especially choose to watch television. And the lack of clarity Sanctions obtained if it violates these rules.Keywords: State Relations and Religion, Program, Policy, Magrhib Recite